The Influence of the Human Development Index and PMDN on Labor Absorption in DKI Jakarta Province - Ria , Anita; Zainuddin, Didi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
This Study is aimed at proving whether there is a relationship that influences the independent variables (HDI) and (PMDN) on the dependent variable Y (Labor Absorption) in DKI Jakarta Province. This research method uses descriptive quantitative research, multiple regression analysis with a correlational approach to time series data. From the test results for individual correlation, it was found that the HDI variable had a significant partial/individual effect on Labor Absorption and the PMDN variable had a partially/individually significant influence of PMDN on Labor Absorption in DKI Jakarta. Simultaneous analysis/joint F test between all independent variables on the dependent variable (HDI and PMDN) together has a significant influence on the dependent variable (Labor Absorption) in DKI Jakarta in the period 2002 - 2021.